New medical schools in Sub-Saharan Africa –a cross-sectional survey of educational structures, operations, and policies - Shah, Krish; Rose, Elizabeth S.; Rees, Andrew; Falayi, Seun; Eichbaum, Quentin (Frontiers in Education, 2023)
Introduction: Africa does not have enough doctors despite having the highest continental burden of disease. Encouragingly, many new medical schools are opening and have begun to graduate doctors. However, the educational structures, operations, and policies of these schools remain poorly understood. This study aimed to better understand these dimensions of new medical schools on the continent. Methodology: We developed and implemented an online survey covering topics that included admissions policies, curricular design, assessment, accreditation, faculty development, research capacity, postgraduate training, and COVID-19-specific challenges. The survey was sent to 130 schools of which 52 represented individually identifiable email addresses (the remainder being schools’ websites or generic addresses). Results: Responses represented ten countries (response rate ~56%). Curricula were mostly lecture-based (n=18, 75%). Electronic platforms and information technologies were used by over 75% (n=18) of schools. More than half have not implemented postgraduate training programs (n=13, 57%). Most schools had a formal accreditation process (n=16, 70%), but the source of accreditation varied. The biggest challenge facing schools was financial (n=20, 87%) followed by faculty/staff recruitment, training, and retention (each n=15, 65%). Conclusion: New medical schools in Sub-Saharan Africa are a gateway to the next generation of medical doctors in a region where medical professionals are desperately needed. This survey of new schools is an important step in better understanding their status and needs, especially with the onset of the pandemic.